Alphabet Recognition with Augmented Reality Technology Based on Android Using Extreme Programming Model - Fitri Yanti; Jaka Sutresna (JUITA : Jurnal Informatika, 2022)
Lack of literacy or interest in reading is the cause of children having difficulty recognizing the letters of the alphabet and assembling them into words or sentences because the letters are similar. Early childhood students have difficulty learning letters because there are too many letters of the alphabet that must be memorized, the number of letters of the alphabet there are 26 letters that must be memorized. In addition, early childhood students complain that reading is very difficult to pronounce because the way the teacher conveys reading techniques for students is difficult to understand so that it is boring for early childhood students. This makes it difficult for young children to pronounce letters. In software development using Extreme Programming (XP) where writing programs in pairs, two programming people work together to write programs. Currently, computer vision technology has been used in various industries, including trade, medicine, education, and so on. Augmented reality is one of the computer vision technologies. The technology of computer vision is to combine synthetic images into the real world or vice versa. By making an android application with an extreme programming method that utilizes Augmented Reality technology that can display 3D, animation, and sound so that it looks real, it makes early childhood interested and makes it easier for them to learn the letters of the alphabet.